2015
DOI: 10.1542/peds.2014-2363
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physician Scorecards on Emergency Department Resource Use, Quality, and Efficiency

Abstract: BACKGROUND AND OBJECTIVES: Variability in practice patterns and resource use in the emergency department (ED) can affect costs without affecting outcomes. ED quality measures have not included resource use in relation to ED outcomes and efficiency. Our objectives were to develop a tool for comprehensive physician feedback on practice patterns relative to peers and to study its impact on resource use, quality, and efficiency. METHODS:We evaluated condition-specific resource use (laboratory tests; imaging; antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…The most common diagnoses previously reported at ED return visits—fever, respiratory infections, and gastroenteritis—are all self‐limited acute medical conditions commonly treated in outpatient as well as ED settings and thus appropriate for a trial of outpatient management. Our findings are also consistent with pediatric studies that have found poor reliability of ED return visits as a performance measure in its lack of correlation with other ED process measures such as rate of radiographic study utilization and physician treatment time …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most common diagnoses previously reported at ED return visits—fever, respiratory infections, and gastroenteritis—are all self‐limited acute medical conditions commonly treated in outpatient as well as ED settings and thus appropriate for a trial of outpatient management. Our findings are also consistent with pediatric studies that have found poor reliability of ED return visits as a performance measure in its lack of correlation with other ED process measures such as rate of radiographic study utilization and physician treatment time …”
Section: Discussionsupporting
confidence: 90%
“…Children represent a unique population to consider given differences in the clinical conditions for which they are commonly cared for in the ED and differences in how pediatric care is delivered. Previous work has challenged the construct validity of return visits as a measure of ED care quality for children—these include chart review studies that find the majority of ED return visits and ED return admissions are due to progression of illness or patient's noncompliance with care rather than poor quality of initial ED care and secondary data analyses demonstrating the poor reliability of ED return visits as a performance measure compared with other ED process measures . Other studies have challenged the common practice of tracking only same‐hospital ED return visits—these studies show that 12% to 32% of 72‐hour return visits among adults and all‐ages populations do not occur at the same hospital as the index visit …”
mentioning
confidence: 99%
“…For example, variability in emergency department clin icians' adherence to available evidence-based clinical guidelines, risk tolerance, clinical decision-making and efficiency may affect both emergency department crowding and patient outcomes. [27][28][29] Another variable of interest, which we could not access for this study, was inpatient hospital occupancy rates at the time of emergency department index arrival. The impact of not including these variables as potential confounders is difficult to estimate, as no prior studies have reported on their association with emergency department length of stay and clinical outcome measures.…”
Section: Limitationsmentioning
confidence: 99%
“…This could be achieved using a provider scorecard and a peer-learning feedback system. 21 Practices and institutional consensus of relevant stakeholders should determine whether decision rules are needed and which rules are the most appropriate. Auditing both impact and adherence to rules should also be part of this process.…”
Section: Risksmentioning
confidence: 99%